(untitled) (International Journal of Engineering and Computer Science, 2017)
The telephone services are supported using LAN as the access network which is an emerging service. The software implementation of a telephone private branch exchange on the LAN connection allows the attached telephones to make calls and to connect other telephone services including Public Switched Telephone Network, Voice over Internet Protocol services and Voice over LAN services. It is well known that IEEE 802.11 WLAN is highly inefficient for transporting voice data. So boosting the voice capacity over multiple WLANs is therefore an area that deserves further attention from the research community. Due to this, the proposed scheme is that simple software upgrades to enhance the VoIP services.